HUBUNGAN ANTARA PEMENUHAN KEBUTUHAN ISTIRAHAT TIDUR DENGAN KEJADIAN HIPERTENSI PADA MASYARAKAT DI DUSUN CELEP KIDUL KELURAHAN DAGEN KECAMATAN JATEN KARANGANYAR - Wiwin Winarni; Pradian Yoga Hartanto (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractSleep is a period of time which is needed for human body to repair the organ cells andbody system in order to work optimally. Based on the preface study conducted by thereseacher, some peoples in Celep Kidul have been suffered from hypertension. Wheninterview was conducted, they mentioned that their time for sleeping less than 7 hours perday. The purpose of this study was to analyze the correlation between sleep needs withthe incidence of hypertension of peoples in Celep Kidul.The subject who used was peoples in Celep Kidul. This research used analytic withcorrelation design. The total population involved in this research were 65 peoples ofCelep Kidul region. Depend on Krecjie table, the total samples involved were 56 peoples.Sampling technik used was purposive sampling. Data was collected by usingquessionairres and measuring blood preasure of the peoples to collect data ofhypertension. The data was analyzed by using chi square statistic.There were two main results of this study : 1) The majority peoples of Celep Kidulshowed that they had abnormal data of sleep needs was 73,21%. 2) The total number ofrespondens who suffered from hypertension was 71,42%. It can be concluded that thesleep needs has related to incidence of hypertension of peoples in Celep Kidulregion (p=0,013).Keywords: sleep needs, hypertension